Preserved single muscle fiber specific force in facioscapulohumeral muscular dystrophy. (17th March 2020) - Lassche, Saskia; Voermans, Nicol C.; van der Pijl, Robbert; van den Berg, Marloes; Heerschap, Arend; van Hees, Hieronymus; Kusters, Benno; van der Maarel, Silvère M.; Ottenheijm, Coen A.C.; van Engelen, Baziel G.M.
Abstract : Objective: To investigate single muscle fiber contractile performance in muscle biopsies from patients with facioscapulohumeral muscular dystrophy (FSHD), one of the most common hereditary muscle disorders. Methods: We collected 50 muscle biopsies (26 vastus lateralis, 24 tibialis anterior) from 14 patients with genetically confirmed FSHD and 12 healthy controls. Single muscle fibers (n = 547) were isolated for contractile measurements. Titin content and titin phosphorylation were examined in vastus lateralis muscle biopsies. Results: Single muscle fiber specific force was intact at saturating and physiologic calcium concentrations in all FSHD biopsies, with (FSHDFAT ) and without (FSHDNORMAL ) fatty infiltration, compared to healthy controls. Myofilament calcium sensitivity of force is increased in single muscle fibers obtained from FSHD muscle biopsies with increased fatty infiltration, but not in FSHD muscle biopsies without fatty infiltration (pCa50 : 5.77–5.80 in healthy controls, 5.74–5.83 in FSHDNORMAL, and 5.86–5.90 in FSHDFAT single muscle fibers). Cross-bridge cycling kinetics at saturating calcium concentrations and myofilament cooperativity did not differ from healthy controls. Development of single muscle fiber passive tension was changed in all FSHD vastus lateralis and in FSHDFAT tibialis anterior, resulting in increased fiber stiffness. Titin content was increased in FSHD vastus lateralis biopsies; however, titin phosphorylation did not differ from healthy controls. Conclusion: Muscle weakness in patients with FSHD is not caused by reduced specific force of individual muscle fibers, even in severely affected tissue with marked fatty infiltration of muscle tissue.